Traductions françaises du Canzoniere de Pétrarque - Barthouil, Georges (Cuadernos de Filología Italiana, 2005)
In the framework of the reception in France of Petrarch’s poetry, the author analises the translations of he nzionere into French, mainly those of Gramont (1842), Genot (1969), de Blanc (1988) and Boilllet nd Rochon 1994). He compares the four translations of the songs «Vergine bella», «Italia mia» y Valle che dei lamenti iei…», praising the most recently published one, but regretting the scarse attention payed to Petrach’s poetic works by the French publishers.